Comparison of Maternal and Fetal Complications Between Teenage Pregnancies and Pregnancies of the age of 20-26 Years - Maryam Naeem, Ayesha Ilyas, Faiza Nawaz, Nayab Afzal, Raheela Ambreen, Samina Asghar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare maternal complications between teenage pregnancies and pregnancies of the age of 20-26 years. Material & Methods: This cohort study was carried out in DHQ/GMC Teaching Hospital Gujranwala during March 2021 till August 2021. Non probability purpose sampling technique was used. Total 200 patients were included in study and divided into two groups. Teenage patients assigned as Group A and group B assigned to patients of age 20-26 years. Both groups assessed for maternal outcomes, antepartum, intrapartum and postpartum complications noted and compared. Results: The following complications were observed among teenage compared with adult pregnancy; anemia (39% versus 18%), hypertension (15% versus 6%), preterm labor (21% versus 9%), prolonged labor (8% versus 29%), and postpartum hemorrhage (13%versus 13%). The results were statistically significant (p-value < 0.05). Conclusions: The complications related to teenage pregnancy are high. These can be avoided by establishing contraceptive strategies.